The relationship between neutrophil to lymphocyte ratio and SYNTAX score in patients with ST-segment elevation myocardial infarction. Issue 2 (2014) - Acet, Halit; Ertaş, Faruk; Bilik, Mehmet Zihni; Kayan, Fethullah; Akil, Mehmet Ata; Aydin, Mesut; Akyuz, Abdurrahman; Yuksel, Murat; Aycicek, Hilal; Ozbek, Mehmet; Oylumlu, Mustafa; Yildiz, Abdulkadir; et al.
No abstract available